Neuro-ophthalmological abnormalities in neurological diseases of dogs and cats: a retrospective study of 114 cases (2010-2015) - BRISIMI (ΝΙΚΟΛΕΤΤΑ-ΜΑΡΙΑ ΜΠΡΙΣΙΜΗ) N. M.; LIATIS (ΘΕΟΦΑΝΗΣ ΛΙΑΤΗΣ ) Th. K.; KOMNENOU (ΑΝΑΣΤΑΣΙΑ ΚΟΜΝΗΝΟΥ) A.; CHARALAMBIDOU (ΓΛΥΚΕΡΙΑ ΧΑΡΑΛΑΜΠΙΔΟΥ) G.; SOUBASIS (ΝΕΚΤΑΡΙΟΣ ΣΟΥΜΠΑΣΗΣ) N.; POLIZOPOULOU (ΖΩΗ ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. S. (Journal of the Hellenic Veterinary Medical Society, 2018)
The current retrospective study includes 99 canine and 15 feline cases with neurologic disease accompanied by neuro-ophthalmological abnormalities (blindness, strabismus, nystagmus, anisocoria, miosis, mydriasis, Horner’s syndrome). All cases were presented in the Companion Animal Clinic of the School of Veterinary Medicine – Faculty of Health Sciences (Aristotle University of Thessaloniki) over a six-year period (2010-2015). The most frequent presenting complaints were head tilt (n=22/99) and paresis/paralysis (n=22/99) in dogs and head tilt (n=3/15) and ataxia (n=3/15) in cats. The most common neuro-ophthalmological abnormalities were strabismus (n=55/99) in dogs and anisocoria (n=7/15) in cats. The localization of lesions was found to be multifocal (n=38/99), and focal, in the vestibular system (n=37/99) in dogs, whilst in cats it was solely multifocal (n=6/15). An etiological diagnosis was reached only in 48 dogs and 10 cats; the former were mainly diagnosed with distemper encephalitis (10/48) and congenital hydrocephalus (6/48) and the latter mostly with encephalitis (n=5/10). Neuro-ophthalmological cases reached a 18.24% of the total neurologic case load (n=625) admitted during a six-year period. Neuro-ophthalmological examination as well as the correlation of the observed abnormalities with the overall neurological symptomatology is important for the neuroanatomic diagnosis, the assessment of severity and prognosis of the respected mainly diseases.